Reassessing the role of mitochondrial DNA mutations in autism spectrum disorder - Carracedo Ángel; Cuscó Ivón; Mosquera-Miguel Ana; Álvarez-Iglesias Vanesa; Pérez-Jurado Luis; Salas Antonio (BMC, 2011)
Abstract Background There is increasing evidence that impairment of mitochondrial energy metabolism plays an important role in the pathophysiology of autism spectrum disorders (ASD; OMIM number: 209850). A significant proportion of ASD cases display biochemical alterations suggestive of mitochondrial dysfunction and several studies have reported that mutations in the mitochondrial DNA (mtDNA) molecule could be involved in the disease phenotype. Methods We analysed a cohort of 148 patients with idiopathic ASD for a number of mutations proposed in the literature as pathogenic in ASD. We also carried out a case control association study for the most common European haplogroups (hgs) and their diagnostic single nucleotide polymorphisms (SNPs) by comparing cases with 753 healthy and ethnically matched controls. Results We did not find statistical support for an association between mtDNA mutations or polymorphisms and ASD. Conclusions Our results are compatible with the idea that mtDNA mutations are not a relevant cause of ASD and the frequent observation of concomitant mitochondrial dysfunction and ASD could be due to nuclear factors influencing mitochondrion functions or to a more complex interplay between the nucleus and the mitochondrion/mtDNA.